Dampak Konsumsi Metil Egenol terhadap Perilaku dan Keberhasilan Perkawinan Lalat Buah Bactrocera carambolae (Diptera: Tephritidae) - Suryati Syamsudlin Tati-Subahar (Jurnal Perlindungan Tanaman Indonesia, 1999)
Methyl eugenol (= ME) is an insect attractant. It is known that male Bactrocera dorsalis is attracted to ME. The objective of this research is to examine the effects of ME consumption on mating behavior and its success of Bactrocera carambolae. Observations were done daily from 17.00 to 18.00 hours. Mating success was characterized by the occurrence of copulation between male and female flies while mating behavior analysed by their fight intensities and wing vibrations. The results showed that the fighting and wing vibration periods of ME consuming flies were longer than those which did not. Mating success of those flies which fed on ME was relatively higher. It was concluded that ME is a stimulant for enhancing mating success of Bactrocera carambolae.